Peculiarities of autoimmune polyglandular syndromes in children and adolescents - Zirilli, Giuseppina; Santucci, Simona; Cuzzupè, Chiara; Corica, Domenico; Pitrolo, Elda; Salzano, Giuseppina (Acta Biomedica Atenei Parmensis, 2017)
Background: no reviews have specifically addressed , to now, whether autoimmune polyglandular syndromes (APSs) may have a peculiar epidemiology and phenotypical expression in pediatric age Objectives: to review the most recent literature data about the specific epidemiological and clinical peculiarities of APSs in childhood and adolescence Design: the main features of the different APSs in pediatric age were compared among them. Conclusions: 1) Among the different APSs, the one that is most typical of pediatric age is APS-1; 2) APS-1 is not characterized only by the classical triad (chronic moniliasis-hyposurrenalism-hypoparathyroidism) and its clinical spectrum is enlarging over time; 3)APS-2 may have a different epidemiological and clinical expression according to two different nosological classifications.